1997
DOI: 10.1002/(sici)1098-2795(199706)47:2<222::aid-mrd14>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B1 expression in meiotically competent and incompetent goat oocytes

Abstract: To start determining the nature of meiotic incompetence in goat oocytes, we have examined the expression of one of the potential pre-MPF subunits: the cyclin B1. We have been isolating a small DNA probe encoding the goat cyclin B1 box to analyze the expression of the cyclin B1 gene in competent and incompetent goat oocytes. This probe was easily obtained by polymerase-chain-reaction (PCR) on reverse-transcribed mRNA from granulosa cells, using cyclin B specific primers derived from a bovine cDNA. The transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Cyclin B is newly synthesized in the presence of actinomycin D 30 min PI, but not in the presence of cycloheximide. Thus it is likely that cyclin B is also newly produced in medaka eggs from cyclin B mRNA that has already been synthesized and accumulated at the end of the growth phase of the oocyte, as reported for the mouse (Hue et al 1997).…”
Section: Discussionmentioning
confidence: 74%
“…Cyclin B is newly synthesized in the presence of actinomycin D 30 min PI, but not in the presence of cycloheximide. Thus it is likely that cyclin B is also newly produced in medaka eggs from cyclin B mRNA that has already been synthesized and accumulated at the end of the growth phase of the oocyte, as reported for the mouse (Hue et al 1997).…”
Section: Discussionmentioning
confidence: 74%
“…In ruminants, cyclin B1 is expressed in granulosa cells and in the oocytes in goat ovary (Hue et al. ), and the involvement of cyclin B1 in oocyte maturation has been reported (Robert et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In ruminants, cyclin B1 is expressed in granulosa cells and in the oocytes in goat ovary (Hue et al 1997), and the involvement of cyclin B1 in oocyte maturation has been reported (Robert et al 2002). In bovine ovary, the granulosa layer of healthy follicles had a significantly higher frequency of proliferating cell nuclear antigen (PCNA)-positive cells than the early and advanced atretic follicles (Feranil et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the regulation of bovine MPF activity is different from other species and provides a useful experimental system to study cyclin B1 function. In both goat and pig GV stage oocytes, both cyclin B1 and p34 cdc2 protein are detected (Christmann et al, 1994;Hue et al, 1997;Dedieu et al, 1998). In mouse GV stage oocytes cyclin B1 protein can be detected, but it is the translation of p34 cdc2 that is partly associated with meiotic competence (Chesnel and Eppig, 1995;de Vant'ery et al, 1996;de Vantery et al, 1996;Kanatsu-Shinohara et al, 2000).…”
Section: Introductionmentioning
confidence: 99%